2001
DOI: 10.1016/s0014-5793(01)02257-8
|View full text |Cite
|
Sign up to set email alerts
|

The C‐terminus of dUTPase: observation on flexibility using NMR

Abstract: The dynamics of the C-terminus of the dUTPases from Escherichia coli and equine infectious anaemia virus (EIAV) were studied by 1 H^1 5 N nuclear magnetic resonance spectroscopy. The two enzymes differ with regard to flexibility in the backbone of the 15 most C-terminal amino acid residues, some of which are conserved and essential for enzymic activity. In the bacterial enzyme, the residues closest to the C-terminus are highly flexible and display a correlation time in the nanosecond time range. No similar hig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

2
21
1

Year Published

2003
2003
2011
2011

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(24 citation statements)
references
References 27 publications
2
21
1
Order By: Relevance
“…This conformational change is realized by intricate subunit interactions as the C terminus of one subunit crosses over its neighboring subunit and adopts an ordered conformation to contact the substrate bound in the active site of the third subunit. In the bacterial enzyme, detailed functional investigations (2,30,33,34), in agreement with the crystal structure in complex with the nucleotide dUDP (28), indicate that the ␥ phosphate of the substrate is indispensable in inducing the closed conformer, and after catalytic cleavage the active site pops open. In the case of the human enzyme, the crystal structure suggests the retaining of the closed conformer even with the product dUMP (24), but there are no functional data published.…”
supporting
confidence: 55%
See 1 more Smart Citation
“…This conformational change is realized by intricate subunit interactions as the C terminus of one subunit crosses over its neighboring subunit and adopts an ordered conformation to contact the substrate bound in the active site of the third subunit. In the bacterial enzyme, detailed functional investigations (2,30,33,34), in agreement with the crystal structure in complex with the nucleotide dUDP (28), indicate that the ␥ phosphate of the substrate is indispensable in inducing the closed conformer, and after catalytic cleavage the active site pops open. In the case of the human enzyme, the crystal structure suggests the retaining of the closed conformer even with the product dUMP (24), but there are no functional data published.…”
supporting
confidence: 55%
“…Conformational Shifts in the C Terminus Are Induced Differently in Drosophila and E. coli dUTPases-Detailed studies from several laboratories unanimously indicated that the ordering of the C terminus of E. coli dUTPase requires interaction with the complete triphosphate chain of the substrate (28,30,34). In the present work, experimental evidence from limited proteolysis, CD spectroscopy, and DSC argue in agreement that dUMP and dUDP are also capable of inducing a significant conformational change (an increment in ordered protein conformation) upon binding to D. melanogaster dUTPase.…”
Section: Discussionmentioning
confidence: 99%
“…The sequence of the C-terminal motif V shares a limited number of features with those of the P-loop motifs (Fig. 1A) (3, 4) present in a large number of ATPase and GTPase enzyme families known as P-loop NTPases including kinases, cytoskeleton and DNA motors, membrane pumps, and transporters.It has been shown that the C terminus of dUTPase is necessary for dUTP hydrolysis but not for nucleotide binding or structural integrity (3,(5)(6)(7). Surprisingly, the active site architecture with bound substrate in the crystal structure of the C-terminally truncated inactive enzyme is identical to that of the wild-type (WT) (7).…”
mentioning
confidence: 99%
“…It has been shown that the C terminus of dUTPase is necessary for dUTP hydrolysis but not for nucleotide binding or structural integrity (3,(5)(6)(7). Surprisingly, the active site architecture with bound substrate in the crystal structure of the C-terminally truncated inactive enzyme is identical to that of the wild-type (WT) (7).…”
mentioning
confidence: 99%
“…Correspondingly, amino acid sequences of the ordered and disordered segments of the C-terminal portions of the E. coli and human enzymes are compared in Table 1. In the E. coli enzyme the C-terminal region is ordered only on binding 2Ј-deoxyuridine with a 5Ј-triphosphate group in the presence of a divalent metal ion (9,10,14). Because ordering of the C-terminal region of the polypeptide chain has been shown to be required for catalytic action by the enzyme (9-11), an approach must be adopted for structural analysis that can be applied to macromolecules in solution.…”
mentioning
confidence: 99%